Experimental Study on the Effect of Flow Velocity and Slope on Stream Bank Stability (Part I) - Jawad Kadhim; Mohanned Q. Waheed; Haitham A. Hussein; Saad F. A. Al-Wakel (Salehan Institute of Higher Education, 2024)
The erosion of riverbanks is a significant and capricious national concern. The Al Muwahada channel in Iraq experiences instability in its banks, resulting in failure, retreat, and morphological alterations. These issues are mostly caused by factors such as the velocity of the flow, the angle of the slope, and type of soil. This study investigated the behavior of canal bank soil in response to erosion and variations in slope angle. Therefore, a physical model of a case study was established in the laboratory. Additionally, a slope angle of 26˚ is being utilized, which has not been previously studied in the laboratory. This angle will be tested with five different velocity values: 0.101 m/s, 0.116 m/s, 0.12 m/s, 0.13 m/s, and 0.135 m/s. The bank's deformation was measured for a period of 12 hours, which was divided into 4 equal intervals for each velocity. The study determined that a riverbank with a slope of 26˚ is more resistant to erosion when the velocity of the water is below 0.12 m/s. Velocities equal to or greater than 0.12 m/s have a substantial impact on the erosion of the riverbed. According to this study, a velocity of 0.12 m/s or higher leads to increased erosion of the riverbank. This is equivalent to a velocity of 0.804 m/s in the prototype channel. The section of the riverbank that has suffered the greatest damage due to erosion is the upper two-thirds. The used methodology supports global efforts to increase information about the behavior of river banks with unexplored rivers that have different flow velocities and bank slope angles. Doi: 10.28991/CEJ-2024-010-08-013 Full Text: PDF